Pembelajaran Berbasis Alam untuk Kemampuan Problem Solving Anak Usia Dini - Reni Amiliya; Anung Dryas M (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2020)
Problems always exist throughout human life, including early childhood. Early childhood are required to be able to solve each of their own problem properly. Currently there are still children who have not been able to solve the problems they face without the help of teachers or other adults. To overcome this problem, researchers proposes nature-based learning to develop children's problem solving abilities. This learning offers children as active learners who are free to play and explore so that they will gain their own experience and knowledge directly. The experience and knowledge gained is used by children to overcome the problems they encounter. The effectiveness of nature-based learning was evaluated by designing learning activities carried out by the quasi-experimental method for 36 children. Two variables: nature-based learning and problem solving abilities. The results showed that there was a significant increase in the problem solving ability of early childhood by 86.11%.